Assessing the effect of public social expenditure and human capital development on Malaysian economic growth: A bound testing approach - Sapuan, Noraina Mazuin; Sanusi, Nur Azura (2010)
Government expenditure on social services is essential to the development of the economy. This fact also applies to Malaysia, a developing country that aspires to become a developed nation in few years to come. As Malaysian government plays a dominant role in financing public education and health services, an analysis on its investment in these areas, if made available, would be able to assist policymakers in generating a strategic plan to enhance human capital development and economic growth. Hence, the aims of this study are to investigate the long run and short run relationships between economic growth and public social expenditure with human capital indicators in Malaysia, using annual data from 1975 to 2008. The cointegration technique - bound testing approach developed within the autoregressive distribution lag (ARDL) framework is utilized.The finding shows that there is a cointegration between economic growth and the explanatory variables.